Ética nos ambientes virtuais no contexto da educação profissional e tecnológica de nível médio - Menezes, Elano da Silva de (2023)
This study is situated within Research Line 2 of ProfEPT, which focuses on the "Organization and Memories of Pedagogical Spaces in Professional and Technological Education (PTE)." Within this research line, it is affiliated with Macroproject 5, addressing the organization of an all-round syllabus in PTE. The overarching objective of this research was to comprehend the role of ethics in the relationships established by students in High-School Professional and Technological Education (HS-PTE) within virtual learning environments and social networks, engaging in a discourse that connects this phenomenon with an all-round human development, a fundamental pillar of PTE. This study adopts a phenomenological approach with a qualitative orientation. Data were collected through bibliographic and documentary research, as well as the administration of questionnaires to participants, Students and teachers of the third year of the technical course in computing integrated with High-School at the Conceição do Araguaia Campus of the Federal Institute of Pará (IFPA). The collected data, when feasible, were subjected to analysis in accordance with the methodology of content analysis. The findings corroborated the hypothesis that students exhibit distinct behaviors contingent upon the mode of interaction. These results served as the foundation for the development of an ethics guide for virtual environments, an educational product aimed at contributing to the Integral Human Formation. of HS-PTE students.